Teachers’ Perceptions of a Successful Transition Program - Hoggatt, Paul (Southwest Baptist University, 2019)
This quantitative study focused on teacher perception of student engagement in a one-to-one technology initiative. Missouri teachers working in a district having freshmen transition program were surveyed to determine their perception of academic achievement, stress and emotional discomfort, and social adjustment of freshman students. Teacher perceptions were analyzed to compare scores between teachers of freshmen and teachers of upper classmen. Also analyzed were scores between male and female teachers. Independent samples t-test suggest no statistically significant difference between how teachers of upper classmen perceive higher success levels of freshmen students resulting from a transition program than teachers of freshmen. The independent samples t-test for gender revealed that female teachers perceive higher success levels of freshmen students resulting from a transition program.